Fenomena Regresi Demokrasi:Potret Demokrasi Masa Kini di Indonesia dan Australia - Asshiddiqie, Jimly (JIMLY LEGAL YUSTISIA JOURNAL, 2023)
The countries of Indonesia and Australia are experiencing what is known as "democratic regression". This discussion is within the scope of factors influencing the decline in the quality of democracy and the legacy of feudal culture as well as the challenges of institutionalization and modernization. Based on the results of the discussion above, it can be concluded that first, there are 6 (six) things that have hit the world which have an influence and contribute to the decline in the quality of democracy throughout the world, which also influence the performance of democracy and the rule of law, especially in Indonesia, including: : a) the emergence of a wave of racism and Islamophobia throughout the world; b) expanding hate speech, hostility, disinformation and miscommunication in public spaces; c) symptoms of political deinstitutionalization; d) the development of the practice of conflicts of interest between business and politics; e) the emergence of a new trend where the 4 forces called "macro quadro politica" which include "state, civil society, market, and the media" move towards one-handed grasp of power; and f) the threat of the spread of the Covid-19 virus being hijacked and misused to make state decisions that are not participatory and ignore the importance of the principles of "deliberative democracy" and substantive public participation. Second, democracy as a mechanism for managing a free market political system must be guarded by mutually agreed values and norms, namely the constitution as a social contract, a national agreement anywhere in the world, although it must be acknowledged that it has many weaknesses, so it is necessary to develop the practice of constitutional democracy, namely democracy that managed based on the highest agreed values and norms within the nation and state.